Shaping perceptions: the effects of public affairs education on the perceptions of good public servants - Tan, Celeste Wei Wei (Nanyang Technological University, 2024)
The effects of public affairs education are a prominent research subject for scholars and an utmost concern for government worldwide. However, there are insufficient studies conducted on the effects of public affairs education. Existing research largely focuses on the career-related outcomes, despite the general agreement that the value of public affairs education lies in its ability to cultivate soft skills in students. Therefore, this study attempts to fill up the research gap to investigate the effects of public affairs education on shaping students’ perceptions of good public servants. Using a questionnaire jointly designed by public affairs professors in Singapore, China and Taiwan universities, data were collected from students before and during their course of study. Our findings primarily indicate that public affairs education, alone and when interacted with other variables such as parents’ influence, does have an impact on students’ perceptions which paves the way for further research to be conducted.